Placing Social Marketing in the Practice of Corporate Social Responsibility: Focusing on Environmental Issues - Saraiva, Andrea; Pinto, Patrícia (Journal of Tourism, Sustainability and Well-being, 2015)
As the awareness of social problems and environmentally related issues in particular becomes widespread, companies have been called to participate in the resolution of these, given that they are the main economic agents with impacts on the society and on the environment. Considering that corporations face pressures from their stakeholders to contribute to solving the social global issues that are affecting them, this theoretical paper analyses the role of stakeholder theory, a new management paradigm, and the importance of social marketing to achieve the aims of corporate social responsibility (CSR). The key point of this study is the possible contribution of social marketing to ensuring the companies’ voluntary involvement in promoting social and environmental well-being, supporting them to respond to stakeholders’ requests, due to its capacity of providing, over time, quantifiable improvement on social issues. In this context, this study explores the linkage between stakeholder theory, CSR and social marketing concepts, giving particular attention to the social marketing contribution to solving environmental issues.